2011
DOI: 10.1097/acm.0b013e318208289a
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: The Case for Research Justice: Inclusion of Patients With Limited English Proficiency in Clinical Research

Abstract: Persons with limited English proficiency (LEP) constitute a growing portion of the U.S. population, yet they are underrepresented in clinical research. This inherently limits the societal benefits of the research and its generalizability to ethnic populations living in the United States. To illustrate the complexity associated with including LEP participants in clinical research, the authors critically evaluated LEP consent requirements posted on the Web sites of 134 academic health centers in March 2008. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Another example is that paradoxically, despite high incidence of disability among people with diabetes, individuals with diabetes who have a disability are disproportionately excluded from diabetes research because co-occurrence of disability often disqualifies them from clinical trial participation (Moore, 2012). Persons with limited English proficiency often are similarly excluded from research participation (Glickman et al, 2011). Therefore, the extent to which therapeutic and intervention effectiveness are generalizable to these sizeable, medically vulnerable populations is unclear.…”
Section: The Connect Frameworkmentioning
confidence: 99%
“…Another example is that paradoxically, despite high incidence of disability among people with diabetes, individuals with diabetes who have a disability are disproportionately excluded from diabetes research because co-occurrence of disability often disqualifies them from clinical trial participation (Moore, 2012). Persons with limited English proficiency often are similarly excluded from research participation (Glickman et al, 2011). Therefore, the extent to which therapeutic and intervention effectiveness are generalizable to these sizeable, medically vulnerable populations is unclear.…”
Section: The Connect Frameworkmentioning
confidence: 99%
“…Nationally, those with LEP are more likely to live in poverty, have poorer health outcomes (Fields 2016), be less educated (Zong and Batalova 2015), and be underrepresented in clinical research. This underrepresentation of significant portions of the population in clinical trials results in research that may not be generalizable to those excluded populations (Glickman et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic, culturally appropriate translations by native speakers rather than directly translated words, may avoid confusion due to discrepant meanings and cultural cues (Brown 2014). Systemically, federal guidelines and individual IRBs must reconsider policies that address language barriers, especially in the informed consent process, to facilitate research participation by LEP individuals (Resnik 2006; Glickman 2011; Livaudais-Toman 2014). Fear of deportation amongst undocumented immigrants related to research participation has been identified as a source of mistrust and fear (Brown 2014).…”
Section: Discussionmentioning
confidence: 99%
“…32% stated fluency requirements for the person obtaining consent, while 68% did not. [41] Variations in policies for including subjects with limited English proficiency in research can results in unequal treatment of human participants when they lead to differences in the consent process.…”
Section: Unequal Treatment Of Human Research Subjectsmentioning
confidence: 99%